PENERAPAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran IPA Kelas VIII SMP Negeri 10 Lahat) - Novi Ariantini; Turdjai Turdjai (DIADIK, 2020)
This study aims to describe the application of the Experiential Learning model and describe the effectiveness of the application of the Experiential Learning model to increase the responsibility and learning achievement of Natural Science subjects in class VIII of SMP Negeri 10 Lahat. The research method used was Classroom Action Research (CAR) and quasi-experiments. The subjects of this study were eighth grade students of SMP Negeri 10 Lahat in the first semester of the 2019/2020 school year. Data collection methods in this study used the observation sheet Experiential Learning model, responsibility observation sheet, and learning outcomes test. From the results of the study show that the application of the Experiential Learning model can increase responsibility, learning achievement and effectively improve student learning outcomes in science subjects in class VIII of SMP Negeri 10 Lahat